Professionals acting in front of the new coronavirus pandemic: health conditions related to emotional aspects (Research, Society and Development, 2022)
With the COVID-19 pandemic, there was an increase in the stressful load of professionals working in health units, causing them occupational stress and emotional, physical and behavioral changes. In this study, the objective was to describe the emotional aspects related to occupational risks in face of the new Coronavirus that can affect the health conditions of professionals working during the pandemic, in the city of Rondonópolis-MT. This is a study with a quantitative, field and descriptive approach, carried out with 69 professionals who have been working in the Sentinel Units. Data were organized in electronic spreadsheets of the Microsoft Office Excel® program, calculated absolute and relative frequencies, analyzed using descriptive statistics. These were mostly female, being 66 (95.65%); aged